Community engagement and clinical trial diversity: Navigating barriers and co-designing solutions-A report from the "Health Equity through Diversity" seminar series. - Luiza Reopell; Timiya S Nolan; Darrell M Gray; Amaris Williams; LaPrincess C Brewer; Ashley Leak Bryant; Gerren Wilson; Emily Williams; Clarence Jones; Alicia McKoy; Jeff Grever; Adam Soliman; et al. (PLoS ONE, 2023)
Introduction In recent years, there has been increasing awareness of the lack of diversity among clinical trial participants. Equitable representation is key when testing novel therapeutic and non-therapeutic interventions to ensure safety and efficacy across populations. Unfortunately, in the United States (US), racial and ethnic minority populations continue to be underrepresented in clinical trials compared to their White counterparts. Methods Two webinars in a four-part series, titled "Health Equity through Diversity," were held to discuss solutions for advancing health equity through diversifying clinical trials and addressing medical mistrust in communities. Each webinar was 1.5 hours long, beginning with panelist discussions followed by breakout rooms where moderators led discussions related to health equity and scribes recorded each room's conversations. The diverse groups of panelists included community members, civic representatives, clinician-scientists, and biopharmaceutical representatives. Scribe notes from discussions were collected and thematically analyzed to uncover the central themes. Results The first two webinars were attended by 242 and 205 individuals, respectively. The attendees represented 25 US states, four countries outside the US, and shared various backgrounds including community members, clinician/researchers, government organizations, biotechnology/biopharmaceutical professionals, and others. Barriers to clinical trial participation are broadly grouped into the themes of access, awareness, discrimination and racism, and workforce diversity. Participants noted that innovative, community-engaged, co-designed solutions are essential. Conclusions Despite racial and ethnic minority groups making up nearly half of the US population, underrepresentation in clinical trials remains a critical challenge. The community engaged co-developed solutions detailed in this report to address access, awareness, discrimination and racism, and workforce diversity are critical to advancing clinical trial diversity.